2009
DOI: 10.1016/j.ejcts.2009.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of E-cadherin cleavage in reperfusion injury

Abstract: These results suggest that one potential mechanism of lung reperfusion injury involves the cleavage of E-cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is expressed in epithelial tissues but in the normal lung, it is not present in the alveolar liquid lining. Hence, appearance of the soluble fragments of E-cadherin in the lavage fluid is a clear indication of epithelial cell injury [42], [46], [47]. We found the 85 kDa soluble fragments of E-cadherin in the lavage fluid of unventilated animals which is likely due to the combined effects of HCl injury and the lavage process itself (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…It is expressed in epithelial tissues but in the normal lung, it is not present in the alveolar liquid lining. Hence, appearance of the soluble fragments of E-cadherin in the lavage fluid is a clear indication of epithelial cell injury [42], [46], [47]. We found the 85 kDa soluble fragments of E-cadherin in the lavage fluid of unventilated animals which is likely due to the combined effects of HCl injury and the lavage process itself (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Goto et al applied this to a model of lung transplantation in rats and observed that rats with transplanted lungs had a higher level of sE-cad than the sham operated rats (68). Again, no direct evidence implicates a sheddase, but other studies have implicated MMP-7 in rodent lung damage studies (26, 55).…”
Section: Generation Of Se-cadmentioning
confidence: 99%
“…Patients with leukemia (myelogenous, monocytic, lymphatic) have increased levels of sE-cad ( P < 0.01), as do patients with leiomyosarcoma ( P < 0.05) (68). Multiple myeloma patients have five times higher levels of serum sE-cad than control samples ( P < 0.0001) (88).…”
Section: Se-cad Is Present In Patient Fluids In a Variety Of Condimentioning
confidence: 99%
“…Goto et al studied lung IR injury to investigate the role of E-cadherin. They found that E-cadherin concentration and expression are increased and undergo cleavage during IR 17 . Menezes et al studied renal IR.…”
Section: Discussionmentioning
confidence: 99%